Analysis of the Influence of Organizational Culture, Transformational Leadership Style, and Career Development on Employee Performance with Job Satisfaction as an Intervening Variable at the Depok City Kpu Office in 2023 - Nur Siti Hasanah; Suryono Efendi (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The researcher took the title Analysis of the Influence of Organizational Culture, Transformational Leadership Style, and Career Development on Employee Performance with Job Satisfaction as an Intervening Variable at the Depok City KPU Office in 2023. The sample size was 150 respondents. The analysis method used is quantitative using SmartPLS. The results showed 1) Organizational Culture, Transformational Leadership Style and Career Development have a positive and significant effect on Job Satisfaction; 2) Organizational Culture and Career Development have a positive and insignificant effect on Employee Performance; 3) Transformational Leadership Style and Job Satisfaction have a positive and significant effect on Employee Performance; 4) Job Satisfaction successfully mediates positively and significantly the influence of Organizational Culture, Transformational Leadership Style and Career Development on Employee Performance.